Incubator Control System Automatic Temperature Stabilizer Bangkok Chicken with LM35 Sensor - Indrawati, Elsanda Merita; Prahesti, Fidya Eka; Maulidina, Miftakhul; Suwardono, Agus; Prasetyo, Kartika Rahayu Tri; Puspitasari, M. Dewi Manikta; Anggoro, Fanny (DPTE FT UNY, 2024)
Many cases of death of chicks in farmers are caused by drastic changes in temperature which result in stress and death of chickens. In this study the authors made a chick coop design equipped with an LM35 sensor which functions to control the temperature of the chicks. The research object is Bangkok chicken aged 7-10 days which has a temperature requirement of 300oC. The test results show that the temperature stabilizer incubator for both the sensor test separately and the integration of the incubator control system as a whole works according to the program design, this is based on the test results that the lights and fans work according to the LM35 sensor reading input with 100% accuracy where as long as 3 days of testing the average temperature of the first, second and third days is below 300oC so that the output is in the form of lights on and the fan is off. On Day 3 all the chickens were healthy and growing well.